1977
DOI: 10.1007/bf00121973
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of atmospheric acoustic sounding at Calgary

Abstract: Operation of a monostatic acoustic sounder on the campus of The University of Calgary for the period March to September, 1976, has provided data on the atmospheric boundary layer over Calgary. The formation and dissipation of the nocturnal temperature inversion layer leaves a clear signature in the sounder records. A trend is discerned in which the nocturnal layer tends to form at sunset, whereas convective instability is established some 2-3 hours after sunrise. Comparison of sounder records with an extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Both reinforce the findings in studies by Goroch (1976), Hicks et al (1977) and von Gogh and Zib (1978). (3) The heights of the lifted inversion The facsimile record sometimes shows an isolated echo layer as shown in Fig.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Both reinforce the findings in studies by Goroch (1976), Hicks et al (1977) and von Gogh and Zib (1978). (3) The heights of the lifted inversion The facsimile record sometimes shows an isolated echo layer as shown in Fig.…”
Section: Resultssupporting
confidence: 88%
“…This relationship has been studied by many researchers; Cronenwett et al (1972), Wyckoff et al (1973), Fukushima et al (1974, Parry et al (1975), Hicks et al (1977) and Clark et al (1977). The most common feature for each record is a weed type echo which is obtained during daytime with strong insolation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the theoretical work of Tatarskii (1961) and Monin (1962), wherein acoustic scattering in air was considered to depend primarily on fluctuations in temperature and wind velocity, and using the Kolmogrov spectrum of turbulence, Little (1969) expressed scattering cross section as a function of scatter angle and structure parameters of wind and temperature fluctuations. Investigations comparing the height of the ground-based sodar echograms with the simultaneously recorded height of the inversion layer using in situ techniques have shown that the acoustic sounder can be confidently used to measure inversion heights for single, unambiguous ground-based layers (Wyckoff et a/., 1973;Goroch, 1976;Hicks et al, 1977;Von Gogh et al, 1978;Singal et al, 1979;Singal et al, 1986).…”
Section: Theorymentioning
confidence: 99%